Effects of $γ$ irradiation on the electric conduction of PZT ceramic system - Zachariasz, R.; Rymarczyk, J.; Ilczuk, J. (Archives of Acoustics, 2006)
In the work, the results of investigations of the electric conduction $\sigma$ of the PZT ceramicswith the two following compositions: Pb$_{0.94}$Sr$_{0.06}$(Zr$_{0.5}$Ti$_{0.5}$)O$_{3}$ + 0.25% wt. Cr$_{2}$O$_{3}$(hard material) and (Pb$_{0.9}$Ba$_{0.1}$)(Zr$_{0.53}$Ti$_{0.47}$)O$_3$ + 1.67% wt. Nb$_2$O$_5$ (soft material), arepresented. The “soft” ceramics are characterized by high electric values ($\epsilon^T_{33}/\epsilon_0 > 1300$(in room temperature), $d_{31} = 120 \cdot 10^{−12}$ C/N) and electromechanical coupling coefficient($k_p > 0.5$). Due to good parameters it is used in electromechanical transducers of low frequency.The “hard” PZT ceramics, which are used in resonators, filters and ultrasound transducersare characterized by the following parameters: $\epsilon^T_{33}/\epsilon_0 > 900$ (in room temperature),$d_{31} = 65\cdot 10^{−12}$ C/N and electromechanical coupling coefficient $k_p > 0.35$. The temperaturedependences of the electric conduction $\sigma$ for all samples before and after $\gamma$ irradiation withdose of 20 kGy were performed. The activation energy $E_a$ was calculated on the basis of theln $\sigma = f(1/T)$ dependences.